PENGARUH KOMPETENSI DIGITAL, ORGANIZATION CITIZEN BEHAVIOUR (OCB) DAN RELIGIUSITAS TERHADAP KINERJA TENAGA KEPENDIDIKAN DENGAN MOTIVASI INTRINSIK SEBAGAI VARIABEL MEDIASI - Mailukni Mailukni; Sulistyandari Sulistyandari; Alum Kusumah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of Digital Competence, Organizational Citizenship Behavior (OCB), and Religiosity on the Performance of Educational Staff at Muhammadiyah University of Riau, with Intrinsic Motivation as a mediating variable. This research employed a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through the SmartPLS application. The population of this study consisted of all educational staff at Muhammadiyah University of Riau, with a total sample of 135 respondents determined using the census technique. The results of the study indicate that: 1) Digital competence has a positive and significant effect on the performance of educational staff. This means that the higher the level of digital competence, the higher the resulting performance. 2) Organizational Citizenship Behavior (OCB) has a positive and significant effect on the performance of educational staff. This shows that extrarole behavior is able to improve work performance. 3) Religiosity does not have a significant effect on the performance of educational staff. Therefore, religiosity does not directly improve performance. 4) Intrinsic motivation has a positive and significant effect on the performance of educational staff. Intrinsic motivation is the most dominant factor in improving performance. 5) Digital competence has a positive and significant effect on intrinsic motivation. This means that improving digital competence strengthens individuals’ internal drive at work. 6) Organizational Citizenship Behavior (OCB) has a positive and significant effect on intrinsic motivation. Voluntary behavior and extra contributions strengthen the internal motivation of educational staff. 7) Religiosity has a positive and significant effect on intrinsic motivation. The higher the level of religiosity, the higher the individual’s intrinsic motivation. 8) Intrinsic motivation significantly mediates the effect of digital competence on the performance of educational staff. Digital competence improves performance through increased intrinsic motivation. 9) Intrinsic motivation significantly mediates the effect of OCB on the performance of educational staff. OCB improves performance both directly and through intrinsic motivation. 10) Intrinsic motivation significantly mediates the effect of religiosity on the performance of educational staff. Religiosity influences performance indirectly through intrinsic motivation (full mediation)